UNIVERSITY OF PUBLIC SAFETY OF THE REPUBLIC OF UZBEKISTAN - Murakayeva Shakhnoza Khayrullayevna (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: Shadowing, a technique originally used in language learning, has evolved into a versatile teaching method applicable across various educational fields. This paper explores the principles, applications, and benefits of shadowing methods in teaching. It examines the effectiveness of shadowing in language acquisition, professional training, and cognitive development. The study also discusses challenges associated with shadowing and offers recommendations for optimizing its implementation.